THE USE OF THE PICTURE AND PICTURE LEARNING MODEL BASED ON JIGSAW PUZZLES TO IMPROVE LEARNING MOTIVATION IN HISTORY LEARNING IN GRADE X SMAN 1 PERANAP: Penggunaan Model Pembelajaran Picture and Picture Berbasis Jigsaw Puzzle untuk Meningkatkan Motivasi Belajar pada Pembelajaran Sejarah Kelas X SMAN 1 Peranap - Zaer Fahmi, Zaer yasa; Isjoni; Yanuar Al Fiqri (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2026)
History learning at SMAN 1 Peranap is still dominated by lecture methods, resulting in low student learning motivation reflected in their minimal participation and attention. This condition encourages the need for the implementation of interactive and visual learning models. This study aims to examine the effectiveness of the Picture and Picture model based on Jigsaw Puzzle in increasing the learning motivation of class X students through the Classroom Action Research (CAR) approach of the Kemmis and Mc Taggart model. Data were collected through questionnaires and observations, then analyzed descriptively quantitatively and qualitatively. The results of the study showed an increase in learning motivation from an average of 62.9 in cycle I to 78.72 in cycle II, so it can be concluded that this model is effective in increasing student learning motivation in history learning.